DIGITAL LEADERSHIP IN ARTS EDUCATION FOR TRANSFORMING TEACHING AND LEARNING IN HIGHER EDUCATION - Huong , Ha Thanh; Tri, Nguyen Quoc; Hoan, Tran Huu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study examines the role of digital leadership in transforming teaching and learning in arts education within higher education in Vietnam. A mixed-method approach was employed, combining survey data from 212 students with semi-structured interviews involving 20 lecturers and academic leaders across three universities. The findings indicate that digital leadership was implemented at a moderate to high level (M = 3.67) and significantly influenced pedagogical transformation (β = 0.58, p < .001). Qualitative results reveal that digital leadership promotes student-centered learning and digital creative practices, but its implementation remains uneven and often relies on individual initiatives. Key challenges include limited digital culture, insufficient professional development, and difficulties in adapting practice-based arts education to digital environments. The study proposes a multidimensional framework of digital leadership and highlights the need for a context-sensitive approach that balances technological innovation with the experiential nature of arts education in Vietnam.